Retention of skull anatomy knowledge in dental education: a comparative study - Thune, Noora Helene; Tostrup Kristensen, Anna; Khan, Qalbi; Utheim, Tor Paaske; Lewi Hammer, Hugo; Sehic, Amer (Frontiers in Dental Medicine, 2025)
There is limited evidence regarding the retention of essential basic science knowledge among dental students and professionals. Understanding the anatomy of the skull, osteology, is crucial as it provides the structural framework essential for comprehending head anatomy, where various soft tissue components are organized. This study aims to evaluate and compare the retention of osteological knowledge across different stages of dental education and professional practice. Specific anatomical structures on selected skull bones and the complete cranium, taught at the pre-clinical level and including clinically and radiographically significant landmarks, were marked for assessment. The study evaluated the ability of second year and fifth year undergraduate dental students, as well as postgraduate students at various stages of specialist training in different dental fields, to independently identify these marked anatomical structures. The study demonstrated significantly higher identification accuracy among second year students compared to fifth year and postgraduate students (p < 0.05). Second year students achieved over 90% accuracy for individual skull bones, with slightly lower accuracy for the entire cranium (85.9%). Fifth year students showed markedly lower retention, with accuracy below 50%, ranging from 20.8% (cranium) to 48.3% (mandible). Postgraduate students performed similarly to fifth year students, notably with only 11.8% accuracy for the sphenoid bone. Significant differences in accuracy were observed among postgraduate specialties (p < 0.05), with oral surgery and oral medicine specialists achieving the highest accuracy (81.2% for the mandible). However, no significant correlation between years of experience and accuracy was observed among the postgraduate groups (p = 0.45). Our results indicate that clinically and radiologically relevant anatomical knowledge is better retained over time, while overall osteological knowledge significantly declines. This highlights the need for strategies beyond initial learning to enhance long-term retention. Integrating clinical, radiological, and surface anatomy into continuing dental education could substantially improve knowledge retention. Furthermore, our findings suggest potential benefits from increased vertical integration and encourage broader discussion regarding the traditional separation between pre-clinical and clinical training phases.